Indonesian Language Learning Based on Local Wisdom - Aditya Permana; Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Indonesian language learning must be taught by every student in Indonesia. Where Language is a media of introduction for humans to understand each other, because language is a tool in communicating between humans. Language is a nation’s culture. Local wisdom is a tradition that lives in society. Local wisdom is a legacy from ancestors. In this article aims to examine Indonesian language learning based on local wisdom, This research uses a literature review method, where the data sourced from scientific journals, articles, books and other reference. The references data was selected, analyzed, and presents in sentences. The result showed that students’ environments and local literature can be subject matter in Indonesian language learning, the use of local wisdom as a learning resource will improve listening, speaking, reading and writing skills, Indonesian language learning based on local wisdom can also maintain the existence of local culture, so that is not forgotten and not drowned by the foreign language. In addition, the use of local literacy can give the impression and effect for students to behave in accordance with the character of local wisdom. In this case, every local wisdom can be guarded, known and preserved by the millennial generation as nation’s next generation.